Design and simulation of an operational amplifier with rail-to-rail input and output voltage swing - Low, Hong Liang (2017)
In this final year project, the author has undertaken the project of designing and simulating an operational amplifier that is capable of rail-to-rail input and output voltage swing. The op amp uses a nested current mirror structure that is highly symmetrical. The finalised architecture was a single stage op amp that uses both NMOS and PMOS transistors for the input. The overall transconductance variation is about 5% operating on the weak inversion region. The op amp can go rail-to-rail on the inputs and outputs that is capable of driving almost all capacitive loads with unconditional stability. Furthermore, it also has very low offset voltage and high CMRR and PSRR.